Integrated Network Pharmacology Analysis and Experimental Validation to Elucidate the Mechanism of Acteoside in Treating Diabetic Kidney Disease - Zhang SJ; Zhang YF; Bai XH; Zhou MQ; Zhang ZY; Zhang SX; Cao ZJ; Wang L; Ding SW; Zheng HJ; Liu YN; Yu GY; et al. (Dove Medical Press, 2024)
Shu Jiao Zhang,1,2,* Yi Fei Zhang,1,2,* Xue Hui Bai,1,2 Meng Qi Zhou,1,2 Ze Yu Zhang,1,2 Shuai Xing Zhang,1,2 Zi Jing Cao,1,2 Lin Wang,1,2 Shao Wei Ding,1,2 Hui Juan Zheng,1,2 Yu Ning Liu,1- 3 Guo Yong Yu,1 Wei Jing Liu1- 3 1Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 2Key Laboratory of Chinese Internal Medicine of Ministry of Education, Beijing Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 3Renal Research Institution of Beijing University of Chinese Medicine, Beijing University of Chinese Medicine, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Guo Yong Yu, Dongzhimen Hospital, Beijing University of Chinese Medicine, No. 5 Haiyuncang, Beijing, Dongcheng District, 100700, People's Republic of China, Email 18901133535@163.com Wei Jing Liu, Renal Research Institution of Beijing University of Chinese Medicine, and Key Laboratory of Chinese Internal Medicine of Ministry of Education and Beijing, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People's Republic of China, Tel/Fax +86-010-84013190, Email 1977@hotmail.comBackground: Acteoside, an active ingredient found in various medicinal herbs, is effective in the treatment of diabetic kidney disease (DKD); however, the intrinsic pharmacological mechanism of action of acteoside in the treatment of DKD remains unclear. This study utilizes a combined approach of network pharmacology and experimental validation to investigate the potential molecular mechanism systematically.Methods: First, acteoside potential targets and DKD-associated targets were aggregated from public databases. Subsequently, utilizing protein-protein interaction (PPI) networks, alongside GO and KEGG pathway enrichment analyses, we established target-pathway networks to identify core potential therapeutic targets and pathways. Further, molecular docking facilitated the confirmation of interactions between acteoside and central targets. Finally, the conjectured molecular mechanisms of acteoside against DKD were verified through experimentation on unilateral nephrectomy combined with streptozotocin (STZ) rat model. The underlying downstream mechanisms were further investigated.Results: Network pharmacology identified 129 potential intersected targets of acteoside for DKD treatment, including targets such as AKT1, TNF, Casp3, MMP9, SRC, IGF1, EGFR, HRAS, CASP8, and MAPK8. Enrichment analyses indicated the PI3K-Akt, MAPK, Metabolic, and Relaxin signaling pathways could be involved in this therapeutic context. Molecular docking revealed high-affinity binding of acteoside to PIK3R1, AKT1, and NF-κB1. In vivo studies validated the therapeutic efficacy of acteoside, demonstrating reduced blood glucose levels, improved serum Scr and BUN levels, decreased 24-hour urinary total protein (P< 0.05), alongside mitigated podocyte injury (P< 0.05) and ameliorated renal pathological lesions. Furthermore, this finding indicates that acteoside inhibits the expression of pyroptosis markers NLRP3, Caspase-1, IL-1β, and IL-18 through the modulation of the PI3K/AKT/NF-κB pathway.Conclusion: Acteoside demonstrates renoprotective effects in DKD by regulating the PI3K/AKT/NF-κB signaling pathway and alleviating pyroptosis. This study explores the pharmacological mechanism underlying acteoside's efficacy in DKD treatment, providing a foundation for further basic and clinical research.Keywords: DKD, acteoside, network pharmacology, experimental verification